CARBACYLAMIDOPHOSPHATES OF THE METALS AS BUILDING BLOCKS FOR SYNTHESIS OF POLYNUCLEAR COORDINATION COMPOUNDS (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
Some of coordination chemical properties of carbacylamidophsphate (CAPh) type ligands - P, N-substituted structural analogues of β-diketones- are presented. It has been shown, that unsaturated d- and f-metals complexes of the composition MLor ML, (were M- d- or f-metal ion, L-CAPh ligand in deprotonated form) may be used as building blocks for the synthesis of bi-,tetra- and polynuclear compounds.
Keywords: -